Performance Analysis of the Behavior Based Safety Program in Reducing Occupational Accident Rates - Mitha Qurrota Ayuni; Muhammad Yusuf; Endang Dwiyanti (The Indonesian Journal of Occupational Safety and Health, 2022)
Introduction: PT. X is a company that concentrates on the agricultural sector by producing ammonia and urea fertilizers. Occupational accidents at PT.X are reported and recorded by the Department of Occupational Health and Safety, one of which is a form of monitoring the performance of the BBS program at PT. X. The research objective was to determine the performance of the Behavior-Based Safety (BBS) program in reducing occupational accidents due to unsafe actions at PT.X. Methods: This study is an observational study. Determination and sampling in this study used accidental sampling technique for safety officers as many as 5 respondents, while the cluster sampling technique was used for the workforce of 95 respondents. The data analysis method used was descriptive semi-quantitative. Results: The results showed the fulfillment of the criteria and maturity level of behavior-based safety at PT. X, In general, PT X was already at level 4, namely "High Performing" with an average of 3.5. Meanwhile, the work accident rate analysis using the Safe T-score of PT. X was in the category between +2.0 and -2.0, meaning that the number of occupational accidents at PT. X after implementing behavior-based safety did not experience any significant changes. Conclusion: The performance of the behavior-based safety (BBS) program in reducing occupational accidents due to unsafe actions at PT. X in 2019 was effective even though the maturity level of the application of BBS was still not at the high performance level criteria on all criteria, and there was still no significant change in the reduction of the number of occupational accidents.